البنية الصوتية ودلالاتها في نص شعار الصرخة - الدعاني , ثابت صالح ' (Journal of Amran University, 2022)
The current research is supposed to study the phonetic structure in the text of the slogan “The Scream for Ansarullah” that was launched by Mr. Hussein Badr Al.Deen Al.Houthi. The purpose of this study is to identify the radical components of the phonemic structure and its characteristics as well as to indicate its impact and role in highlighting and enriching the meaning, as well. Moreover, this research aims to reveal the connotations, feelings and suggestions that are inspired by the Scream as an extent of their proportionality, coalition and harmony with the linguistic structure, in general, in the text of Scream slogan.On the light of this, the researcher has depended on the descriptive and analytical approaches in purpose to achieve the previous objectives. To clarify these approaches, the descriptive approach was apparently provided by a voice description of the essential elements of the phonemic structure through using statistics in purpose to provide numerical data that formed the essential in the applied study and the elucidation of semantics. While the analytical approach was also based on dismantling the vocal structure into its constituent elements as consonant sounds, vowel sounds, and voice clips. Accordingly, the research is divided into the three following topics; Consonant Sounds and their Connotations, Vowel Sounds and their Connotations, and Voice Clips and their Connotations retrospectively. It is noted that the previous topics were preceded by an introduction, including the concept of the phonetic structure and a presentation of the slogan text. Additionally, the research exposes the historical background of the slogan text and a statement of its importance and functional role. To sum up, the researcher has concluded that the composition of the phonetic structure according to the phonetic characteristics and the pronunciation features of the phonetic components of the slogan text “The Scream” was the most appropriate and optimal for the slogan text “The Scream” in content and performance. Consequently, the Scream reflects the creative linguistic ability in its systems, the control of the colors of its sounds, the selection of its words and the structure of its sentences, and the comprehensiveness and depth of its connotations.